Who tended to continue smoking after cancer diagnosis: the national health and nutrition examination survey 1999-2008 - Tseng Tung-Sung; Lin Hui-Yi; Moody-Thomas Sarah; Martin Michelle; Chen Ted (BMC, 2012)
Abstract Background It has been estimated that there are approximately 12 million cancer survivors in the United States. Continued smoking after a cancer diagnosis is linked to adverse effects among cancer survivors on overall survival, treatment effectiveness, and quality of life. Little is known about who is more likely to quit smoking after his/her cancer diagnosis. The objective of this study is to evaluate factors associated with smoking cessation in cancer survivors, which to date has not been well studied. Method The National Health and Nutrition Examination Survey (NHANES) 1999-2008 surveys were used in this study. A total of 2,374 cancer survivors aged 20 and over with valid smoking status in the NHANES 99-08 survey were included in this study. Among them, 566 cancer survivors who regularly smoked at the time of their cancer diagnosis were included in the analyses. Results Around 50.6% of cancer survivors smoked regularly prior to their cancer diagnosis and only 36.1% of them quit smoking after their cancer diagnosis. Racial disparity was observed in smoking cessation among cancer survivors. Hispanics (OR = 0.23, 95% CI = 0.10-0.57) were less likely to quit smoking than Whites after their cancer diagnosis. Conclusion Two-thirds of cancer survivors continued smoking after cancer diagnosis. Our study observed that the high risk group of continued smokers among cancer survivors is made up of those who are female, younger, Hispanic, with longer smoking history, underweight or with normal weight and without smoking-related cancer. These findings suggest that smoking cessation for cancer survivors should target on the high risk subgroups.